2014
DOI: 10.7314/apjcp.2014.15.19.8435
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Values of VEGF and Endostatin with Malignant Pleural Effusions in Patients with Lung Cancer

Abstract: Aims: Angiogenesis is important in malignant pleural effusion (MPE) formation and it is regulated by a number of pro-and anti-angiogenic cytokines. The purpose of this study was to evaluate the prognostic value of angiogenic factor vascular endothelial growth factor (VEGF) and angiogenesis inhibitor endostatin in lung cancer patients with MPE, and investigate the relationship between these two kinds of agent. Methods: Using enzyme-linked immunoadsorbent assay, the concentrations of VEGF and endostatin were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…VEGF can be released by both malignant and inflammatory cells, and various studies indicated that VEGF is associated with Regulation mechanism of three high confident target genes and miRNAs, and related biological functions survival and pleurodesis outcomes in MPE [6,13]. Both VEGF and HSP90B1 are critical in the development of MPE by regulating angiogenesis [36]. VEGF has also been used as drug target of Bevacizumab and Cisplatin for the treatment of MPE in advanced stage non-smallcell lung cancer from one clinical trial by Chinese PLA General Hospital (NCT01661790).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF can be released by both malignant and inflammatory cells, and various studies indicated that VEGF is associated with Regulation mechanism of three high confident target genes and miRNAs, and related biological functions survival and pleurodesis outcomes in MPE [6,13]. Both VEGF and HSP90B1 are critical in the development of MPE by regulating angiogenesis [36]. VEGF has also been used as drug target of Bevacizumab and Cisplatin for the treatment of MPE in advanced stage non-smallcell lung cancer from one clinical trial by Chinese PLA General Hospital (NCT01661790).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the activated receptor ERBB4 can also affect glycoprotein PDPN to trigger TFs, GATA3 and FOXO3 through cascade proteins CHIC2, Moesin (MSN), TUBB3, RHOXF2, SMG1 in the signaling pathways, to regulate proliferation through the mediation of FOXO3 , SMG1 , and NF1 , to regulate cell mobility through the mediation of NF1 , to regulate cell adhesion through the mediation of CDH3 , and to regulate lymphangiogenesis through the mediation of VEGFC (Figure 6F). COL18A1 encodes Type XVIII collagen, also known as Endostatin, a potent antiangiogenic protein that is able to inhibit angiogenesis and is associated with malignant pleural effusions in patients of lung cancer [164, 165]. Besides, COL18A1 is a regulator of the oxidative stress response and has been suggested that the potential links between ECM and oxidative stress response in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This was particularly impressive in the subset of patients with non-squamous histology. Bevacizumab is generally well tolerated and does not appear to increase the incidence or severity of nausea/vomiting, neuropathy and renal toxicity, which are typically associated with carboplatin/paclitaxel chemotherapy ( 74 , 88 91 ). Nevertheless, although bevacizumab improves outcomes when added to platinum-based chemotherapy in advanced-stage non-squamous NSCLC, a recent phase III trial study demonstrated that the addition of bevacizumab to adjuvant chemotherapy did not improve overall survival for patients with surgically resected early-stage NSCLC ( 92 ).…”
Section: Vegf In the Prognosis Of Mpe In Various Subtypes Of Nsclc Anmentioning
confidence: 99%